Time-of-Day-Dependent Trafficking and Function of Leukocyte Subsets. Issue 6 (June 2019) - Pick, Robert; He, Wenyan; Chen, Chien-Sin; Scheiermann, Christoph
Abstract : The number of leukocytes circulating in blood in mammals is under circadian control (i.e., ∼24 h). We summarize here latest findings on the mechanisms governing leukocyte migration from the blood into various organs, focusing on the distinct leukocyte subtype- and tissue-specific molecules involved. We highlight the oscillatory expression patterns of adhesion molecules, chemokines, and their receptors that are expressed on endothelial cells and leukocytes, and which are crucial regulators of rhythmic leukocyte recruitment. We also discuss the relevance of clock genes for leukocyte function and migration. Finally, we compare immune cell rhythms under steady-state conditions as well as during inflammation and disease, and we postulate how these findings provide potential new avenues for therapeutic intervention. Highlights: Leukocytes infiltrate tissues in a time-of-day-dependent manner, depending on subset- and tissue-specific rhythms in promigratory factors. Murine neutrophils rhythmically infiltrate many organs and thereby change the phenotype of the respective tissue. Adaptive immune responses, which take weeks to develop, are under circadian control in mice, and strongly depend on the time of day when an initial stimulus is given. Leukocytes can cell-autonomously regulate their circadian oscillations in the murine host by responding to reactive oxygen species and altering the binding of HIF-1α to the clock protein BMAL1, thus governing chemokine CXCR4 expression. Glucocorticoids transcriptionally regulate the expression of the IL-7 receptor in a circadian manner in mice, thus driving rhythmic CXCR4 expression and CD4 + and CD8 + T cell redistribution across the body.